The Importance of Simulation Accuracy in Chaotic Circuits - P. Kvarda (Radioengineering, 2000)
In this paper an example of importance of the simulation accuracy indeterministic chaotic oscillators and other chaotic systems is brieflydescribed and shown. Low accuracy in simulation may cause that thenon-chaotic system may look chaotic or chaotic as non-chaotic. How wecan prevent it is shown also in this work.